DETERMINATION OF A PROMOTIONAL STRATEGY FOR E-COMMERCE COMPETITION IN INDONESIA USING GAME THEORY - Susanti, Desi; Akbar, Y Rahmat (SULTANIST: Jurnal Manajemen dan Keuangan, 2022)
This research aims to determine the expected value of strategy (expected payoff) from the promotional strategies carried out by two Indonesian e-commerce companies, Tokopedia and Shopee. It is intended to generate maximum profit or minimal loss caused by the competition between the two companies through game theory simulation. The research design uses quantitative data with an applied research design. The analytical method used in this research is the Game Theory approach. The data was processed using the POM-QM application for Windows V5.2. The results show that completing the competitive payoff matrix in both e-commerce companies uses a pure strategy. The calculations and data processing results show that the maximum value is the same as the minimum value, which means that the saddle point has been reached and is the Optimal Strategy for the game value of -24.11. Because the game value from the payoff matrix is negative, the game is won by the column player, namely Shopee, using a promotional strategy in the form of free shipping. Meanwhile, to minimize the loss of row players, Tokopedia can use a promotional strategy in the form of cashback